The Effect of School Religious Culture on Students' Emotional Intelligence at State Junior High School - Halima Halima; Fatimah Saguni; Rustina Rustina (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This study aims to find out how religious culture influence the emotional intelligence of students at a Junior High School. This study used quantitative method. The sample of the study was 46 Junior High School students selected randomly. The students were given questionnaires using Likert scale. Validity test was done using Pearson’s Product Moment correlation technique, while the reliability test used Alpha formula. Prerequisite analysis test used normality test and linearity test. The data was analyzed using simple linear regression techniques. The level of significance of the results of the analysis wass determined at 5%. The number of valid items for religious culture variables was 15 items, and the number of valid items for the emotional intelligence variable was 17 items. This study found that religious culture applied at Junior High School (SMP) 10 Sigi effected the emotional intelligence of the students. It was found that the r count value of 0.590 compared to the r table value (0.05 ; 46) = 0, 285. The obtained r count> r table was 0.590> 0, 285, meaning that there is a significant influence. This means the religious culture of the school as an independent variable influences emotional intelligence as the dependent variable and it appears that the implementation of religious culture is more effective to increase the students emotional intelligence.